The impact of cassava wastewater from wet fufu paste processors on surrounding soils: a case study of Ayetoro, Ogun State, Nigeria - Adedotun Temitope Adegoke; Babajide Emmanuel Olowu; Nurudeen Samuel Lawal; Olubunmi Abosede Odusanya; Oluseun Bamidele Banjo; Oluwafemi Babatunde Oduntan; Babasola Dapo Odugbose (Brawijaya University, 2020)
Cassava effluent has become a subject of growing environmental concern in developing countries largely due to ineffective disposal methods. In this study, the impact of land disposal technique by processors in Ayetoro, Ogun State Nigeria was investigated. Soil samples were collected from three disposal sites scattered across the study area at depths of 0 cm, 15 cm, 30 cm and 45 cm. Results were compared with samples obtained from control sites at a distance of 5 m from the disposal sites. The physicochemical parameters determined includes soil pH, silt, sand, clay, organic carbon, exchangeability acid, pH, total nitrogen, average phosphorous, zinc, lead, iron, sodium, copper, calcium, potassium, magnesium and manganese. The result show that the pH varies significantly across the sites. The highest concentration was recorded for phosphorous while the lowest concentration was obtained for total nitrogen. The highest concentrations were recorded at the soil surface while the lowest were recorded at 45 cm depth. Idagba recorded the highest pollutant concentration and while the lowest were obtained at kano. The activities and discharge techniques of processors had negatively impacted the soil quality which may also affect the ground water quality. There is a need to take proactive measures to protect the environment through adequate sensitization and enforcement of environmental laws.